Análisis funcional y simulación del convertidor matricial ca/ca en matriz de conversión directa - Sánchez Parra, Yerson Fabian (Universidad Antonio Nariño, 2021)
Electronic converters play a significant role today, they can be found in the power supplies of computer equipment, smartphones, electric vehicles, TVs, stereos, as well as other household electronics. These converters must guarantee the quality of power when supplying alternating current (AC) or direct current (DC) power, so that the signals generated must contain a low or zero harmonic content, and that they allow a constant power supply to prolong the lifespan of components in electronic equipment. The Matrix Converter (MC) offers features such as: voltage control, frequency control, harmonic content compensation to correct the power factor. These characteristics mean that the MC can be used in a large number of applications both in AC and DC and that is why in this research thesis aims to describe the electronic physical configuration of a three-phase MC, and the direct switching strategy DSVPWM (Direct Vector Space Pulse Width Modulation) used to operate bidirectional semiconductors for a reliable power supply. The performance tests have been developed using Simulink of Matlab.